Strengthening Multiculturalism and the Pancasila Student Profile through Global Partnerships and Mobility in Indonesian Higher Education - Novita, Mega; Sundari, Riris Setyo; Hidayat, Nur; Nugrohadi, Saptono; Bhandari, Rahul (KnE Social Sciences, 2025)
In the era of globalization, integrating international partnerships and mobility within higher education is crucial for fostering innovation, inclusivity, and cross-cultural understanding. This study examines how these elements contribute to the enhancement of the Pancasila Student Profile, which emphasizes character education and student-centered learning, within the framework of Indonesia’s Kurikulum Merdeka. Using an explanatory sequential mixed-methods approach, the research combines qualitative interviews and focus group discussions with quantitative surveys from students and faculty at Universitas PGRI Semarang. The results indicate that 85% of participants gained from cultural exchanges, improving cultural awareness (78%) and collaborative curriculum development (72%). Additionally, international mobility boosted global competence (75%) and reinforced Pancasila values (70%). Key strategies for improvement include enhancing pre-departure orientations, increasing funding for mobility programs, and integrating Pancasila principles into international collaborations. The study highlights the importance of global mobility in strengthening national identity and global competencies. It recommends that higher education institutions prioritize international mobility, integrate global experiences into curricula, and foster an inclusive learning environment.